(untitled) (International Journal of Engineering and Computer Science, 2017)
A Question Answering (Qa) System Provides Direct Answers To User Questions By Consulting Its Knowledge Base. This Paper Presents Basic Architecture Of Qa System That Is Based On Information Retrieval System, Modules And Its Various Types. Along With That This Work Also Describes Different Architectures For Various Types Of Question Answering Mechanism Such As Open Domain Qas, Closed Domain Qas, Rule Based And Web Based Qas. The Comparison Among Different Architectures Of Question Answering Mechanism Is Also Drawn